2015
DOI: 10.3109/00365521.2015.1063155
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible optic neuritis after infliximab treatment in a patient with ulcerative colitis

Abstract: This article reports the first known case of permanent blindness due to irreversible unilateral optic neuritis (ON) related to infliximab (Remicade) treatment of a patient with ulcerative colitis. A young male, with a family history of inflammatory bowel disease, was diagnosed with ulcerative colitis at the age of 20. He was treated with steroids and a 5-aminosalicylic acid drug without considerable effect, and later admitted to our hospital due to a relapse during reduction of the prednisolone dosage. A new c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Optic neuritis The exact number of cases that present ON as an effect of infliximab or other TNF inhibitors is unknown but seems to be much higher than described in the literature [70]. Many reports state the occurrence of optic neuropathy and neuritis during treatment with infliximab [34,[71][72][73][74][75][76][77][78][79]. Most present with bilateral and retrobulbar involvement, but different patterns are described.…”
Section: Infliximabmentioning
confidence: 99%
“…Optic neuritis The exact number of cases that present ON as an effect of infliximab or other TNF inhibitors is unknown but seems to be much higher than described in the literature [70]. Many reports state the occurrence of optic neuropathy and neuritis during treatment with infliximab [34,[71][72][73][74][75][76][77][78][79]. Most present with bilateral and retrobulbar involvement, but different patterns are described.…”
Section: Infliximabmentioning
confidence: 99%
“…Adverse effects of anti-TNF α have been discussed intensively as the possible etiology of new-onset demyelination diseases in patients with IBD. For ON, several case reports have indicated that this may be due to the onset time being close to the start of the anti-TNF α treatment, and the condition was reversed in some cases after discontinuing the use of anti-TNF α agent [22][23][24]29,30]. The issue remains inconclusive and unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al performed a retrospective cohort study and a retrospective cross-sectional study using the data of the era before anti-TNF α treatment (1988 to 1997), and the results demonstrated that regardless of anti-TNF α use, patients with IBD were more likely to have a higher incidence of MS, demyelination and ON compared with a matched control. In a recent retrospective multicenter study of a large database and a comprehensive literature review, Alexandre et al [30] identified 26 cases of optic neuritis from the literature and the European Crohn's and Colitis Organisation's Collaborative Network for Exceptionally Rare case reports (CONFER) database. Sixteen patients were under anti-TNF α treatment, and 10 patients were without anti-TNF-α treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 56 Ophthalmic side effects related to infliximab include uveitis, optic neuritis, and endophthalmitis. 57 , 58 , 70 , 78 88 The association with endophthalmitis is likely related to the immunosuppressive effect of infliximab; it is also theorized that scleral thinning due to scleritis may also increase the risk of endophthalmitis during anti-TNF-α therapy. 84 …”
Section: Growth Factor Modulatorsmentioning
confidence: 99%